Manajemen Sarana dan Prasarana dalam Menunjang Proses Pembelajaran Geografi Studi Kasus : SMAN 2 Tanjung Morawa - Romauli Situmorang; Dwidya Nuari; Mira Susila Warni; Ruth Sahana Manalu; Egi Ateta Barus; Eni Yuniastuti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The management of educational facilities and infrastructure is a process of organizing all facilities to ensure that the educational process in an educational institution can take place effectively and efficiently. The purpose of this study is to determine the management of facilities and infrastructure used to support the learning process in the Geography subject at SMAN 2 Tanjung Morawa. This research uses a qualitative approach. The population and sample in this study are the Head of Facilities and Infrastructure and the Geography teachers at SMAN 2 Tanjung Morawa. Data in this study were collected through interviews, documentation, and literature review. Subsequently, the data were analyzed using thematic analysis techniques. The results of this study indicate that the management of facilities and infrastructure at SMAN 2 Tanjung Morawa is still suboptimal in terms of planning, procurement, utilization, management, and evaluation systems, resulting in the geography learning process at this high school still relying on lecture methods and manually visualizing geography lessons using a blackboard.